AN ENVIRONMENTAL COMPARISON OF PLASTIC AND PAPER CONSUMER CARRIER BAGS IN SOUTH AFRICA: IMPLICATIONS FOR THE LOCAL MANUFACTURING INDUSTRY - Sevitz, J.; Brent, A.C.; Fourie, A.B. (The South African Journal of Industrial Engineering, 2011)
ENGLISH ABSTRACT: The conventional consumer carrier bags have recently received considerable attention in South Africa. The choice of material for these bags, based on environmental preferences in the South African context, could significantly influence the local manufacturing industry. Life Cycle Assessment (LCA), an environmental management tool, has been applied to objectively evaluate and compare the overall environmental impacts of the complete life cycles (from raw material extraction to final disposal) of consumer plastic and paper carrier bags in South Africa. Paper bags have a higher carrying capacity compared to plastic bags and different use ratios were subsequently evaluated. Plastic bags have a lower environmental impact for use ratios of up to 2.5 plastic bags to one paper bag. Above this ratio the conclusions are not reliable. Paper bags would need to increase its recycled content significantly to be competitive in terms of environmental impacts. The re-use of thicker plastic, as proposed by the new plastic bag legislation, has the potential to significantly lower the impact of plastic bags. AFRIKAANSE OPSOMMING: Die konvensionele gebruikersdrasakke het onlangs aansienlike aandag in Suid Afrika ontvang. Die keuse van materiaal vir hierdie sakke, wat gebaseer is op omgewingsvoorkeure in die Suid-Afrikaanse konteks, kan ’n wesenlike invloed uitoefen op die plaaslike vervaardigingsindustrie. Lewenssiklusanalise (LCA), ’n omgewingsbestuurgereedskap, is aangewend vir ’n objektiewe evaluasie en vergelyking van die algehele omgewingsimpakte van die totale lewenssiklus (vanaf grondstofekstraksie tot finale wegdoening) van gebruikersplastiek- en papierdrasakke in Suid-Afrika. Aangesien papiersakke ’n ho